Institutional Drivers of Policy Fragmentation: A Case of The Borobudur World Heritage Site, Indonesia - I Made Krisnajaya; Janianton Damanik; Ely Susanto (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2026)
Policy fragmentation is often treated as a taken-for-granted phenomenon without sufficient critical efforts to further explain the underlying factors. This tendency leads to an incomplete understanding and creates a knowledge gap in advancing the state of the art of policy fragmentation. This study aims to explore and analyse the underlying causes that contribute to policy fragmentation in the governance of tourism destinations. Using a qualitative exploratory approach, the study focuses on the governance of the Borobudur World Heritage Site as a single case. Data was collected through a comprehensive literature review and in-depth interviews with key stakeholders involved in Borobudur’s conservation and commercialisation activities. The findings show that policy fragmentation arises from institutional pressures, institutional segmentation, and the commodification of policy object. These factors have shaped the governance dynamics of Borobudur over the past three decades. This study deepens understanding of the institutional drivers of policy fragmentation and strengthens the case for making fragmentation a central concern in policy studies. The findings should help policymakers and analysts to better identify and reduce the negative effects of policy fragmentation. Future research should explain the dynamics of the fragmentation process and its institutional consequences.